The effect of ASEAN economic integration on foreign direct investment. - Ismail, Normaz Wana; Smith, Peter; Kugler, Maurice (Sejong University, Sejong Institution, Center for International Economics, 2009)

(untitled)
The primary concern of this study is to highlight AFTA’s roles in increasing ASEAN countries’ attractiveness for FDI from members and non-members, noting that the agreement has been followed by many packages to enhance FDI flows into the region. The time period cover in this study is after the AFTA has been implemented (1995 to 2003). The gravity model is employed in this study in the analysis based on cross section and panel data analysis. There are two main effects are considered in this study, namely the effects of REI on intra-regional FDI flows and on extra-regional FDI flows. The major finding of this study is the ASEAN5 invest in each other less than they invested in the new ASEAN members. The empirical results from extra-regional-FDI revealed that the European countries increase investment in ASEAN than any other region in the sample. Moreover, further investigation also found that the USA and Japan invested more in ASEAN5 than in the new ASEAN members.